2018
DOI: 10.4274/jus.2046
|View full text |Cite
|
Sign up to set email alerts
|

Are the Complication Rates for the Open Approach in the Surgical Treatment of Bladder Stones Higher Than Rates for Endoscopic Approaches? A Comparative Multivariate Analysis Study

Abstract: What's known on the subject? and What does the study add? The complication rates for open surgical approaches are significantly higher than the rates for endoscopic approaches in the management of bladder stone disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…In another more recent study, success rates of endoscopic and open surgical techniques were reported as 92.5% and 100%, respectively. Again in the same study, authors concluded that open surgery presents higher complication rates than the endoscopic approach (19). Currently, it is well known that open surgery is the technique of choice for limited indications such as cases with oversized bladder stones or those, who are scheduled to undergo simultaneous prostatectomy or diverticulotomy (20).…”
Section: Resultsmentioning
confidence: 93%
“…In another more recent study, success rates of endoscopic and open surgical techniques were reported as 92.5% and 100%, respectively. Again in the same study, authors concluded that open surgery presents higher complication rates than the endoscopic approach (19). Currently, it is well known that open surgery is the technique of choice for limited indications such as cases with oversized bladder stones or those, who are scheduled to undergo simultaneous prostatectomy or diverticulotomy (20).…”
Section: Resultsmentioning
confidence: 93%